Clinical and laboratory characteristics of patients presenting to a tertiary care center emergency department with invasive group A streptococcal infections. Issue 3 (May 2020) - Dudar, Karly; Littlefield, Shalyn; Garnett, Meghan
ABSTRACT: Objectives: The aim of this study was to describe the clinical and laboratory characteristics of invasive group A streptococcal infections in a geographic area that sees a high volume of cases. Methods: We conducted a health records review of consecutive patients presenting to the Thunder Bay Regional Health Sciences Centre Emergency Department (ED) in 2016–2017 with a diagnosis of invasive group A streptococcal infection using ICD-10 codes. Patient demographics, host characteristics, triage vital signs, laboratory values, culture sites, and disposition were described using univariate and bivariate statistics. Results: Forty-four adult cases were identified over 2 years, with a median age of 44 years (interquartile range, 35–52). The most prevalent risk factors were diabetes mellitus (45%), current or previous alcohol abuse (39%), and current or previous intravenous drug use (34%). The two most abnormal triage vitals signs were a heart rate ≥ 100 beats per minute in 32 (73%) cases and a respiratory rate ≥ 20 breaths per minute in 27 (63%) cases. The temperature was ≥ 38°C in only 14 (32%) of cases. The C-reactive protein (CRP) was always elevated when measured, and greater than 150 mg/L in 20 (71%) of cases. One-third of patients had an ED visit in the preceding 7 days before the diagnosis of invasive group A Streptococcus . Conclusions: Invasive group A streptococcal infections often present insidiously in adult patients with mild tachycardia and tachypnea at triage. The CRP was the most consistently abnormal laboratory investigation.